Attacking beautifully or defending efficiently? A sociological analysis of the prevalence and effect of football strategies - Seippel, Ø (Soccer & Society, 2018)
Football ideology is built upon an antagonism between offensive and defensive and effective and beautiful football: attack beautifully and lose, or, defend efficiently and win! In this article, I address the validity of this hegemonic understanding and investigate the extent to which (i) modern football actually practises one or the other - scoring goals or avoids conceding - and (ii) how the two strategies actually pay off. The case is 65 years of Scandinavian male football. I start with an overview of numbers of scored goals and variation in scoring. Next, I look at whether success depends on scoring the most or conceding the least. Finally, I analyse how many positions each goal is worth. In general terms, the finding is a defensive trend where modern football has fewer and more valuable goals, but that this trend has clear wavelike patterns, indicating that which strategy being profitable varies.